Effect of Pantoprazole on the Absorption of Hydroxychloroquinea A Randomized Drug‐Drug Interaction Trial in Healthy Adults. Issue 2 (15th July 2021) - Stoll, Felicitas; Blank, Antje; Mikus, Gerd; Czock, David; Foerster, Kathrin I.; Hermann, Simon; Gümüs, Katja; Muhareb, Amin; Hummler, Simone; Sauter, Max; Weiss, Johanna; Burhenne, Jürgen; et al.
Abstract: Hydroxychloroquine as a weak basic compound with two amines is strongly enriched in cell compartments with low pH, suggesting that modification of gastric pH by coadministered proton pump inhibitors might reduce its solubility and absorption and thus its efficacy in patients. We addressed this question in a single‐center, open‐label, randomized, parallel drug‐drug interaction trial in healthy adults (EudraCT No. 2020‐001470‐30). All participants received a single oral dose of 400‐mg hydroxychloroquine, and one group additionally received 40 mg of pantoprazole once daily for 9 days dosed to steady state. Whole‐blood samples were collected for 72 hours, and hydroxychloroquine was quantified by liquid chromatography–tandem mass spectrometry. Primary endpoints were whole‐blood hydroxychloroquine areas under the concentration‐time curve from 0 to 72 hours (AUC0‐72h ) and peak concentrations (Cmax ). Unpaired 2‐sided t ‐tests of the log transformed pharmacokinetic parameters were performed to compare both groups. Twenty‐four participants (12 per group) were included. Hydroxychloroquine AUC0‐72h and Cmax did not differ between groups without and with pantoprazole (arithmetic mean; AUC0‐72h, 7649 ng/ml h, and 8429 ng/ml h, P = .50; Cmax, 448 ng/mL and 451.5 ng/mL, P = .96, respectively). Pantoprazole did not alter hydroxychloroquine absorption, indicating that proton pump inhibitors do not affect its bioavailability.